A genetic algorithms approach to technical analysis on stock exchange - Yu, Hairong; Vilas Wuwongse; Zhao, Ming; Hosomura, Tsukasa; Deutscher Akademischer Austausch Dienst (Bangkok : Asian Institute of Technology, 1991)
In this thesis, the author introduces a method that uses Genetic Algorithms (GAs ) to acquire stock trading rules on machine learning of the expert system. The learned rules support decisions of forecasting the trends of prices, index, moving average lines for buying and selling the stocks. The thesis reports results of experiments with the prototype implementation. These results indicate that Genetic Algorithmsbased learning is good to rules of stock exchange. Moreover, the thesis proposes some considerations for the application. Meanwhile, a package is designed for the customers' trading on stock exchange market.
A thesis submitted in partial fulfi l lment of the requirements for the degree of Master of Science, School of Engineering and Technology
Thesis (M.Sc.) - Asian Institute of Technology, 1991
Keywords: Stock-exchange -- Thailand; Investment analysis